دور حوكمة الشركات في الحد من مخاطر الائتمان في المصارف التجارية الليبية - الشكري , عائشة سالم; الجلالي , سعد عبد السلام سعد (Scientific Journal of University of Benghazi, 2021)
This study aimed to identify the role of corporate governance in reducing credit risk in Libyan commercial banks. The study relied on the descriptive-analytical approach. The study population consisted of Libyan commercial banks, and the sample was limited to banks in which the volume of credit granted exceeds 1% of the total credit volume of the bank. The study used a questionnaire to collect data from the participants, and (80) questionnaires were distributed, of which (61) were returned and all of them were valid for analysis. The Statistical Package for Social Science program was used to analyze the data and the necessary statistical tests were conducted. The study concluded that corporate governance has a role in reducing credit risk in Libyan commercial banks, and there are no significant differences among the participants' opinions in terms of the role of corporate governance in reducing credit risk in Libyan commercial banks which can be attributed to their demographic variables. The study recommended that commercial banks practice corporate governance mechanisms properly in granting credit and highlighted the necessity of adhering to the terms and foundations of the credit policy, concentrating on credit analysis and adequate studies before granting credit.